The study of youth's perception and preference level towards the suburban Youth City - 'Adilah Zafirah binti Azmi (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2018)
The migration of youth towards the urban cities are related to several factors. In dealing with this matter, the government had proposed a Youth City concept to attract youth in residing the suburban area. It emphasizes on the allocation of affordable houses, efficiency in the medium of travel, the availability of facilities as well as employment opportunities. The study further aims to identify the youth's perception and preference level towards the suburban factors and characteristics, influencing them to live in the suburban Youth City. Therefore, there is a need to justify the relationship between the youth's background and their preference living in an area, youth's awareness towards the suburban Youth City concept, and identify the suburban factors and characteristics which influences youth's interests to live in the suburban Youth City. A quantitative data approach had been used with the collection of the questionnaire survey. The sample size for this study is 120 respondents comprises of bachelor's degree students studying in their final year from various public universities which are International Islamic University Malaysia (IIUM), University Malaya (UM) and University Teknologi MARA (UiTM). The main finding reveals that the respondent's preference to live in the urban or suburban area varies based on their background and life transitions. The majority of respondents prefer residing in the urban area after graduating, regardless of their gender, place of origin and current house, location and shifted their preference towards residing the suburban area once they are married. Furthermore, several respondents were initially unaware with the Youth City concept, but apparently 75% of respondents express interests living in the suburban Youth City after the concept had been explained. Both group of respondents that are interested and uninterested towards living in the suburban Youth City mostly agreed with the factors and characteristics of the suburban area. Thereby, increment in the suburban projects that upholds the concept of Youth City while constantly promoting the idea among young people are recommended. The awareness and encouragement for young people to live in the suburban area will be initiated, consequently reducing the overpopulated situation in the urban cities and capitals.